Practices of Management Accounting Techniques in Service Sector Public Enterprises in Nepal - Dhami, Narad Bahadur (Janajyoti Journal, 2024)
Management accounting is the act of making sense of financial and costing data and translating that data into useful information for management and officers within an organization. This research aims at examining the practice of management accounting and the major difficulties in applying management accounting tools in the public enterprises of the service sector of Nepal. It also tries to assess the impact of management accounting system on the performance of sampled organizations. The specific survey research has been followed with a descriptive-analytical approach. A structured questionnaire was used to collect primary data from the respondents which were analyzed by the multiple correlation and regression model. The study employed simple judgmental sampling procedure to draw the samples. Out of the seven public enterprises in Nepal that operate in the service sector five were selected as the samples. The results revealed that there is a significant impact of management accounting systems on organizational performance. The study suggested to implement the effective managerial tools and techniques a separate managerial accounting department should be established within an organization. The study also recommended that academicians who have better knowledge about MA tools and techniques should put in the effort to develop environmentally friendly tools and techniques into practice and also to keep management accounting information system. It helps to keep them informed from time to time about every aspect of MA and its application.